Implementing Problem-Based Learning Models in Social Studies to Improving Students Moral Character - Septia Puspa, Celyna Isnaeni; Sundawa, Dadang (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This article discusses one of the learning models that can be used in schools: Problem-Based Learning (PBL) in social studies learning to foster moral character. Prosocial actions and good and beneficial attitudes can characterize a person's moral character. A vital prerequisite for a country is to have quality and human moral resources (HR) because by doing so, a country will be able to adapt to global problems and increase the nation's competitiveness. The purpose of this research is to determine whether problem-Based Learning (PBL) in social studies learning fosters students' moral character. The method used in this research is a literature study(library research). The data analysis used in this research is content analysis (Content Analysis). Findings from research can be known by using a learning approach Problem-Based Learning (PBL) in social studies learning can help students grow their moral character. Because character building, which seeks to create good and useful citizens, has the same goal as the main goal of social studies learning. ApproachProblem-Based Learning (PBL) in social studies teaching can help students develop moral character, which is indicated by the ability of students to recognize, understand, and work to overcome problems faced by countries that are increasingly complex in a global environment.